New Methods for the Functionalization of Polymer Matrices with Thiomolybdate Clusters Applied for Hydrogen Evolution Reaction Catalysis - Nadine Hannewald (Wiley-VCH, 2021)
The embedding of molecular reactive species such as catalysts into polymers opens up new avenues for advanced composite design for energy technologies and beyond. Herein, two new approaches for the connection of molecular molybdenum sulfide clusters and synthetic polymers are presented. The approach one is based on the utilization of a molecular molybdenum sulfide cluster as a potential chain transfer agent in a free radical polymerization process. The second one is a postpolymerization functionalization of a thiol end‐functionalized polymer with a thiomolybdate cluster. Detailed characterization using Raman spectroscopy reveals the successful functionalization in the latter approach, whereas in the other one, a noncovalent interaction is suggested. Furthermore, visible light‐driven hydrogen evolution demonstrates that the molecular molybdenum sulfide cluster retains its catalytic activity after the combination with polymers.